DAYA DUKUNG LINGKUNGAN DAN KESESUAIAN LAHAN DALAM PENGEMBANGAN PULAU ENGGANO BENGKULU - Senoaji, Gunggung (Bumi Lestari Journal of Environment; Vol 9 No 2 (2009), 2009)
This research is aimed at knowing environmental carrying capacity of Enggano Island, knowing suitability value of land for various activities. Method used is survey method explore environment. The environment carrying capacity is calculated based on comparison between natural resources owned and people need according to established standard, parameter, and indicator. Suitability of land for various needs is based on established criterion and standard. Recently, development in Enggano Island is still under its environmental carrying capacity, both form ecologic and economic aspects. Along with population growth, need of space and natural resource will increase so that it is necessary to determine threshold of environmental carrying capacity. The Enggano Island are suitable to be developed for coastal tourism, nautical tourism, catching fishery, agricultural and plantation, settlement and conservation area. The main problem in development and improvement in Enggano island is fresh water availability that is only derived from rainfall and vegetation cover. Therefore, forest existence as manager and protector of soil water management has to be absolutely exixt and appropriate with it’s location, wide and quality.
Keywords: Enggano Island; carrying capacity; fresh water; suitability of land